THE NOTIONS OF GORAN STEFANOVSKI ON IDENTITY AND IDENTITY NARRATIVES (Philological Studies, 2019)
The paper analyses Goran Stefanovski’s notions on tradition, identity and identity narratives, expressed in the works he wrote after his relocation to Canterbury, Great Britain, at the time when he was already regarded as one of the leading East European playwrights. Unlike James Joyce’s exile, which is characterized by his permanent animosity towards his homeland Ireland and its tradition, Goran Stefanovski’s existence in another geographic, cultural and political context strengthened his affinity towards Macedonian tradition, which he defined as a pillar of the Macedonian identity. At the same time, he perceived his position as existing between two narratives, between two cultures (Macedonian and British), which underlines the necessity for his plays and essays to be interpreted within the context of transnational literature, as they were created and exist between two or more languages and cultural heritages.
Keywords: Goran Stefanovski, identity, narrative, exile, transnational literature